A fotografia na história do Museu de Arte Moderna de São Paulo (MAM-SP): Photography in the history of the Museum of Modern Art of São Paulo (MAM-SP) (Revista de História da UEG (REVHIST), 2020)
This article aims to highlight the importance of photography in the collection of the Museum of Modern Art in Sao Paulo (MAM-SP), both in relation to the historical moments concerning the acquisition of this type of work of art, and by evoking the links that are established with the curators, directors and exhibitions that have legitimized the presence of photography within the museum. The museum's first approach to photography took place through exhibitions in the late 1940s, but the first incorporations of photography works did not take place until the early 1980s, through events focused exclusively on this type of media. Currently, the foundations of the collection are established, and it continues to grow thanks to the incorporations made today by the Club of Photography Collectors, always in search of dealing with the multiplicity of photographic images produced by Brazilian artists.Keywords: Photography. Museum. Collection.  Museum of Modern Art of Sao Paulo.